Paper‐based Analytical Devices: In Situ Nucleic Acid Amplification and Ultrasensitive Colorimetric Readout in a Paper‐Based Analytical Device Using Silver Nanoplates (Adv. Healthcare Mater. 7/2021). Issue 7 (7th April 2021) - Suea‐Ngam, Akkapol; Choopara, Ilada; Li, Shangkun; Schmelcher, Mathias; Somboonna, Naraporn; Howes, Philip D.; deMello, Andrew J.
Abstract : In article number 2001755 by Andrew J. DeMello, Philip D. Howes, and co‐workers, the combination of loop‐mediated isothermal amplification (LAMP) and silver nanoplates allows ultrasensitive colorimetric detection of methicillin‐resistant Staphylococcus aureus (MRSA), down to a single target copy, with easy qualitative readout by the naked eye and quantitative readout with a smartphone camera.